Design and control of a climbing robot for inspection of high mast lighting. Issue 1 (4th February 2019) - Li, Peng; Duan, Xingguang; Sun, Guangli; Li, Xiang; Zhou, Yang; Liu, Yunhui
Abstract : Purpose: This paper aims to develop a climbing robot to help people inspect lamps of high-mast lighting. Design/methodology/approach: The robot consists of driving mechanism, suspension mechanism and compression mechanism. The driving mechanism is realized by link chains and sprockets, which are arranged opposite to each other, to form a dual caterpillar mechanism. The compression mechanism squeezes the caterpillar, and rubber feet "grasps" the steel rope to generate enough adhesion forces. The suspension mechanism is used to compensate the contraction or extension of the chains. The robot is equipped with a DC motor with a rated power of 250 W and a wireless module to communicate with the operator's console. The dynamic model of the robot and the control strategy is derived, and the stability of the controller is proofed. Findings: The payload experiment shows the robot can afford up to 3.7 times payload versus its own weight. Even when the payload is 30 kg, the robot can maintain a speed of the 1 m/s. The experiments also show that the tracking error of the robot reaches zero. Practical implications: The proposed moving mechanism has a high load/weight ratio, which is a verified solution for the cable inspection purpose. Originality/value: A rope climbing robot for high mast lighting inspection is proposed. The developed mechanism can reach a speed of 1 m/s with the payload of 30 kg, while its own weight is only 15.6 kg. The payload/weight ratio of the robot is 2.24; this value is rather good in many climbing robots reported in other renowned journal.